Combining radiotherapy with sunitinib: lessons (to be) learned - Kleibeuker, Esther A. (Angiogenesis, 2015)
To improve the efficacy of radiotherapy (RTx), there is a growing interest in combining RTx with drugs that inhibit angiogenesis, i.e., the process of neo-vessel formation out of preexisting capillaries. A frequently used drug to inhibit angiogenesis is sunitinib (Sutent, SU11248), a receptor tyrosine kinase inhibitor that is currently FDA approved for the treatment of several cancer types. The current review presents an overview of the preclinical studies and clinical trials that combined sunitinib with RTx. We discuss the findings from preclinical and clinical observations with a focus on dose scheduling and commonly reported toxicities. In addition, the effects of combination therapy on tumor response and patient survival are described. Finally, the lessons learned from preclinical and clinical studies are summarized and opportunities and pitfalls for future clinical trials are presented. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10456-015-9476-3) contains supplementary material, which is available to authorized users.